Ki Hadjar Dewantara's View on Freedom to Learn in His Relationship with Character Improvement - Wahyuni, Teti; Usman, Jarjani; Suyanta, Sri (Jurnal Sustainable, 2023)
The development of an intellectually curious and morally upright next generation is one of Indonesia's stated educational objectives. The principle of "freedom of learning" empowers both educators and their pupils to shape the educational system as they see fit. Due to the current emphasis on information rather than competence in Indonesian education, the goal of independent learning is to provide an enjoyable educational experience for both students and instructors. Personal growth in accordance with Indonesian national principles is another focus of Merdeka Belajar. Does education aim to bring about change and improve the environment, as Ki Hadjar Dewantara believes it does, or is it primarily focused on fostering student growth? Starting with bettering the learning system and learning processes, promoting freedom of learning is one way to put the ideals of the nation's personality creators into practice. We think that by allowing people more freedom to study, we can all contribute to making the world a better place.